The Effect of Analytical Thinking and Critical Thinking on Mathematical Problem Solving Ability - Herawati, Herawati; Buditjahjanto, I Gusti Putu Asto; Anifah, Lilik (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Education is an effort to create a basis for developing human resources towards better ones. In the era of the independent curriculum, the educational approach emphasizes the 4C concept which includes Communication, Collaboration, critical thinking and creativity. Vocational school level learning places more emphasis on understanding how students can think critically and analytically. Critical thinking can be formed from the way they reconstruct their knowledge. The research aims to determine the simultaneous influence of analytical thinking and critical thinking skills on problem solving abilities. The research used a sample of 47 class The research uses multiple linear regression analysis for the independent variable (analytical thinking and critical thinking) and the dependent variable (problem solving ability). The results of the ANOVA significance research were 0.000, then the calculated F value was 60.617. Then the R2 value was 0.734. This shows that analytical thinking and critical thinking simultaneously influence mathematical problem solving abilities with a percentage of 73.4%.